Physiology, pathology and the biomolecular corona: the confounding factors in nanomedicine design. Issue 6 (1st February 2022) - Liu, Kai; Salvati, Anna; Sabirsh, Alan
Abstract : Nanomedicines can acquire different biomolecular coronas from various biological contexts. This review offers a practical guide to tuning corona content to match physiological requirements as a necessary step for future nanomedicine success. Abstract : The biomolecular corona that forms on nanomedicines in different physiological and pathological environments confers a new biological identity. How the recipient biological system's state can potentially affect nanomedicine corona formation, and how this can be modulated, remains obscure. With this perspective, this review summarizes the current knowledge about the content of biological fluids in various compartments and how they can be affected by pathological states, thus impacting biomolecular corona formation. The content of representative biological fluids is explored, and the urgency of integrating corona formation, as an essential component of nanomedicine designs for effective cargo delivery, is highlighted.